Relationship of Family Support with Self-Treatment Ability of Schhizoprenia Patients at Tamiang Layang Health Center - Oktavia, Nor Afni; Haspariadi, Haspariadi (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2022)
Introduction: Mental disorder are syndromes or behavioral patterns that are clinically significant and associated with distress or suffering and cause disturbances in one or more functions of human life. The role of the family is very important in the healing process schizophrenic between family support and self-care ability of schizophrenic patients at the Tamiyang Layang Health Center. Method: This research is quantitative with a cross sectional approach. The population of this study amounted to 54 schizophrenia patients in 2020 with a total sampling technique and the sample of this study amounted to 54 people. The collection tool is in the form of a questionnaire. Results: Data analysis using univariate analysis and bivariat analysis with spearman rank test. Family support is included in the category of optimal family support as much as 77,8%. The patient's self-care ability is included in the category of self care ability of a patient, information from the family shows that patients need partial assistance 81,5%. Conclusions: There is a relationship between family support and self care ability of schizophrenic patients at the tamiyang layang health center which is included in the strong category with a P value = 0,000 <0,05 and the correlation is positive because the strength value is 0,777.